Mental health of HIV-infected patients: A severe, but Overlooked Problem - Choi, Jun Yong (The Korean Society of Infectious Diseases and Korean Society for Chemotherapy, 2013)
HIV-infected patients are known to have severe psychosocial problems; however, clinicians tend to overlook these psychosocial issues. Song et al. identified depression and anxiety as the most common mental illnesses among HIV-infected patients. Psychosocial issues are important factors and are associated with poor adherence, which leads to treatment failure and resistance. Clinicians who tend to HIV patients should be attentive to the patients' psychosocial problems and regularly conduct screening for depressive disorders. Mental health must be addressed to improve the quality of life of patients with HIV/AIDS.